Measurement of Physical Fitness Aspects of Lower Limb Muscle Strength in Students Using Wall Squat Test Instruments - Dana Kurniawan; Fajar Hidayatullah; Heni Yuli Handayani; Agus Himawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Leg muscle strength is a very important component as an effort to improve overall physical because leg muscle strength is the main driver of any activity that involves physical activity, especially physical fitness. Muscle Strength serves as a support for all body components and also stabilizes the point of balance when kicking is done by one leg. The purpose of this researcher is to find out how much physical fitness the lower leg muscle strength is in junior high school. Therefore, the author is interested in measuring the physical fitness of lower leg muscle strength. This type of research is descriptive quantitative is to analyze the data by describing or describing the data collected. The population in this study were students of SMPN 1 Bangkalan. The sampling technique in this research is using Quota sampling. The number of samples that will be used in this research are 30 students of Bangkalan 1 State Junior High School. The results of the validity test showed that the wall squad test that was carried out was valid and could be tested on students of SMPN 01 Bangkalan. Obtained Person Correlation 0.848> 0.361 item 1 and 0.843> 0.361 for item 2. Reliability test obtained by Cronbach Alpha of 0.600> 0.361 it can be concluded that the data we test is reliable. used is normally distributed.